Active-only current-mode first-order allpass filter and its application in quadrature oscillator - Jantakun, Adirek; Jaikla, Winai (My University, 2015)
The current-mode first-order allpass filter (APF) using only the active elements has been studied in the present paper. The proposed circuit comprises two operational transconductance amplifiers (OTAs) and one operational amplifier (OA) which is suitable to future development into an integrated circuit. The pole frequency and phase response can be electronically adjusted with changing the dc bias currents of OTAs. The APF has high output impedance, which is easy to cascade in high-order filter or drive load without using a buffering device. The current-mode quadrature oscillator is included to show the usability of the proposed filter. The results of PSPICE simulation are accordant with the theoretical analysis.
Keywords: Active-only APF; Current-mode; First-order allpass filter; Operational amplifier; Operational transconductance amplifiers